1991
DOI: 10.1007/bf02387828
|View full text |Cite
|
Sign up to set email alerts
|

Densification process for spherical glass powders with the same particle size by hydrothermal hot pressing

Abstract: Low-temperature sintering of spherical glass powders with the same particle size was attempted by hydrothermal hot pressing at 260 ~ The microstructure of densified bodies was observed by scanning electron microscope and the existence of water in the surface reaction layer was confirmed by Fourier transform infrared spectroscopy. The reaction layer was formed on the surface of spherical glass particles after hydrothermal hot pressing. The thickness of the layer increased with reaction time. The layer was defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These processes are quite similar to the liquid sintering mechanism of ceramics. Hence, the successful syntheses of bulks of zeolites are thought to be due to the cementation by dissolution of solution of sodium silicate as a mechanism of solidification, although we cannot neglect the solution/precipitation process as well as other previous results of oxide during HHP 11–22 . Further detailed works are now under investigation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These processes are quite similar to the liquid sintering mechanism of ceramics. Hence, the successful syntheses of bulks of zeolites are thought to be due to the cementation by dissolution of solution of sodium silicate as a mechanism of solidification, although we cannot neglect the solution/precipitation process as well as other previous results of oxide during HHP 11–22 . Further detailed works are now under investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Previous papers suggested that the bulk prepared by HHP was solidified by dissolution and precipitation processes 11–22 . Especially, the results of densification of glass powder suggested that shrinkage proceeded by viscous flow mechanism 11,12 . In the HHP process, the zeolite polycrystalline surface was dissolved in NaOH solution on HHP and then dissolved zeolitic gel was made to flow at voids in bulks and finally recrystallized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the curing duration is shorter than the optimal curing duration, an increase in the curing temperature or curing duration causes OH − to bond with additional Si and Al, which are required for geopolymer formation. However, if the curing duration exceeds the optimal curing duration, water molecules and OH − ions may diffuse to the surface of undissolved glass particles and corrode them [34]. The higher the AE%, the more severe this corrosion.…”
Section: Effects Of the Ae% On The Curing Processmentioning
confidence: 99%
“…The schematic of the autoclave, composed of a stainless tube, pistons, packing and an electric heater, for hydrothermal hotpressing [13][14][15] is shown in Fig. 1.…”
Section: Samplementioning
confidence: 99%